Causes of contractors’ claims in international engineering-procurement-construction projects - Shen, Wenxin; Tang, Wenzhe; Yu, Wenyang; Duffield, Colin F.; Hui, Felix Kin Peng; Wei, Yongping; Fang, Jun (Journal of Civil Engineering and Management, 2017)
Engineering-Procurement-Construction (EPC) method has increasingly been applied in international markets. In this research, the causes of contractors’ claims in international EPC projects are modeled and empirically tested with industry survey, structural equation modeling and case studies from the perspective of Chinese contractors. The established model outlines the causes of contractors’ claims as: external risk (sociopolitical risks, economic risks, and natural hazards), clients’ organizational behavior (untimely payment, change orders, and inefficient processing), and project definition in contract (unclear scope of works, and unclear technical specification). The structural equation modelling validates that these causes have direct influences on claim respectively. Besides, clients’ organizational behavior acts as a partial mediation between external risk and claim, demonstrating that external risk can also exert influence on claim through affecting clients’ organizational behavior. Seven case studies further confirmed and interpreted the substantive meaning of these relationships. This study establishes interdisciplinary linkages among knowledge areas of contracting, risk management, organizational behavior, and international EPC project delivery, which has important primary contributions in both theory and practice. Understanding how the fundamental factors interactively lead to claims can help contracting parties to develop effective claim strategies, proactively mitigate project risks, and ultimately improve EPC project performance.